THE MANDIBULAR PERIOSTEUM AS A METASTATIC SITE FOR OROPHARYNGEAL SQUAMOUS CELL CARCINOMA - D. V. Sikorsky; S. O. Podvyaznikov; A. N. Volodin; A. A. Chernyavsky (Опухоли головы и шеи)
The mandibular periosteum is regarded as a metastatic site for oropharyngeal squamous cell carcinoma. This investigation is based on the clinical observations of 152 patients with locally advanced and recurrent oropharyngeal carcinoma, who have undergone surgery as part of combined and combination treatment at the Nizhny Novgorod Regional Oncology Dispensary (Branch One) in the period 2005 to2014. In9 (6 %) patients of them, mandibular periosteal metastases were the only manifestation of disease progression after termination of combined and combination treatment. The metastases were not verified before surgery and their manifestation was not accompanied by a local relapse or regional and distant metastases. In all the 9 patients, the mandibular periosteal metastasis was located in the projection of a previously removed tumor. When the surgery was attended by segmental resection of the lower jaw in the combined and combination treatment of locally advanced or recurrent oropharyngeal carcinoma, the mandibular periosteum to be removed is an effective measure to prevent the spread of periosteal micrometastases that could not be diagnosed preoperatively. Thus, the mandibular periosteum should be considered to be one of the metastatic sites for oropharyngeal squamous cell carcinoma, which must be taken into account when planning an operation in the combined and combination treatment of patients with locally advanced and those with a disease recurrence.